Colour vision of the citrus psylla Trioza erytreae (Del Guercio) (Homoptera: Psyllidae) in relation to alightment colour preferences - Urban, Alan Joseph (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1977)
The colour vision of adult citrus psylla, Trioza erytreae, was investigated in the laboratory using the behavioural parameters: alightment and walking. Light green flushing leaves (under which the nymphs develop) were significantly preferred, visually, to dark green mature leaves for alightment. Diffuse reflectance spectroscopy showed (when expressed in the parameters of human colour vision) that flush has a very slightly longer dominant wavelength, and roughly double the reflectance and purity. Alightrnent frequency correlated almost equally well with "purity" (as noted by Moericke, 1952 et seq., in "yellow-sensitive" aphids) as with the aphidological colour parameter "long/short ratio" developed by Kennedy et al. (1961). Elucidation of the mechanism underlying the citrus psylla's alightment colour preference was initially attempted with a printed spectrum and several paint series of measured spectral characteristics. It was clear that T.erytreae belongs to the "yellow-sensitive" group of Homoptera, but it was impossible to distinguish which pararneter(s) of colour the psyllids were responding to. Phototactic (walking) response to the individual parameters of colour was therefore measured using a monochromator. The phototactic action spectrum (against wavelength) was tri-modal, with peaks in the yellow-green (YG), blue (B), and ultra= violet (UV). Rate of phototaxis was not influenced by bandwidth (roughly equivalent to purity), but was proportional to intensity (roughly equivalent to reflectance). To investigate the influence of the above three wavelength regions on alightment, use was made of a very simple flight chamber incorporating a target of coloured light. Yellow-green and UV light both independently stimulated alightment . Their effect was additive. Different thresholds indicated distinct YG and UV receptor systems. Blue light alone did not stimulate alightment, and was strongly alightment-inhibitory in combination both with YG and with UV light. On the basis of the above physiological/behavioural findings, a new alightment formula was drawn up for describing the hamopteran's apparent manner of alightment determining integration of surface reflectance. The flush preference and alightment distributions on the series of artificial surfaces were found to correlate slightly more accurately, on average, as well as more consistently, with the new formula than with previously-available colour parameters. These findings are placed in perspective to the literature, and their possible economic relevance is discussed.
Keywords: Trioza; Homoptera; Jumping plant-lice; Color vision